2012
DOI: 10.1097/tme.0b013e318251515f
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ED Boarding Time, Severity of Illness, and Discharge Destination on Outcomes of Critically Ill ED Patients

Abstract: This aim of this study was to determine the association between emergency department (ED) boarding time, severity of illness, and outcomes for critically ill patients. This was a prospective cohort study of ED patients who met criteria for admission to the intensive care unit (ICU). Patients were divided into 2 groups: those who spent less than 6 hr in the ED prior to transfer, and those who spent 6 hr or more. The groups were compared on the basis of severity of illness, Glasgow Coma Scale score, presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][32][33][34][35][36][37][38][39][40][41][42][43]48,49,53 All observational studies were cohort studies; all but four were retrospective. 32,42,43,46 Eight studies described interventions to improve care during times of capacity strain, [55][56][57][58][59][60][61][62] none using randomization to assign treatment category. Outcomes for children were separately analyzed in only six of the observational studies 23,26,32,45,46,51 and none of the experimental studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][32][33][34][35][36][37][38][39][40][41][42][43]48,49,53 All observational studies were cohort studies; all but four were retrospective. 32,42,43,46 Eight studies described interventions to improve care during times of capacity strain, [55][56][57][58][59][60][61][62] none using randomization to assign treatment category. Outcomes for children were separately analyzed in only six of the observational studies 23,26,32,45,46,51 and none of the experimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…Studies included in this review used very different terms to describe capacity strain, from general descriptions (e.g., Bstrained,^1 4 Bbusy,^1 5 or high Bworkload^3 1,32,41 ) to descriptions based on the number of admitted patients (e.g., Bcrowding^or Bovercrowding,^2 6,53 high Bcensus^or Boccupancy,^1 7,18,24,35,41,44,47,50 ) to descriptions based on the number of new patients (e.g., Badmission volume^1 9 ). A subset of studies used terms often found in trauma or public health emergency literature (e.g., Bsurge,^1 1 Bmass casualty incident,^2 7 or Bmultiple casualty incident^4 9 ); others used sequelae of high inpatient census to define strain (e.g., BED boarding^1 6,20,21,23,30,38,43 or Btime from receiving the order for a bed and leaving the ED,^2 5 Black of beds^4 2 or Brefused admission due to full unit,^3 6 Bdelayed admission,^4 0 Bboarding^2 2 or Boutlying^4 2 or Bbedspacing^5 2 in non- primary units). This lack of standard terminology contributed to differences in how strain was conceptualized by study authors, i.e., whether it was based on changing patient occupancy, acuity, or turnover or whether it was measured indirectly (Online Appendix).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delayed transfer of critically ill patients from the emergency department (ED) to the medical intensive care unit (MICU) may be associated with longer hospital length of stay (LOS) and increased mortality (1)(2)(3)(4)(5). Major factors leading to prolonged ED to MICU transfers are lack of available beds in the ICU and a shortage of ward beds for stable ICU patients (3).…”
Section: Introductionmentioning
confidence: 99%